The Oxford handbook of comparative administrative law - Cane, Peter, 1950-; Hofmann, Herwig; Ip, Eric Chi Yeung; Lindseth, Peter L. (Oxford : Oxford University Press, 2020)
The comparative study of administrative law has a long history dating back more than 200 years. It has enjoyed a renaissance in the past 15 years or so and now sits alongside fields such as comparative constitutional law and global administrative law as a well-established area of scholarly research. This book provides a broad and systematic view of the subject both in terms of the topics covered and the legal traditions surveyed. In its various parts it surveys the historical beginnings of comparative administrative law scholarship, discusses important methodological issues, examines the relationship between administrative law and regime type, analyses basic concepts such as 'administrative power' and 'accountability', and deals with the creation, functions, and control of administrative power, and values of administration.
Units and Methods of Comparison / Marco D'Alberti -- Comparison within Multi-Level Polities and Governance Regimes / Jacques Ziller -- Negotiating Language Barriers / Edoardo Chiti -- Comparative Administrative Law and Public Administration / Anthony M. Bertelli, Fiona Cece -- Comparative Administrative Law: The View from Political Science / Stefanie A. Lindquist, David M. Searle -- Comparative Administrative Law and Economics / Nuno Garoupa, Sofia Amaral-Garcia -- The Time Dimension in Comparative Research / Bernardo Sordi -- Diffusion, Reception and Transplantation / Mariana Mota Prado -- Parliamentary Regimes / Eric C. Ip -- Presidential Regimes / Gabriel Bocksang Hola -- France: The Vicissitudes of a Tradition / Jean-Louis Mestre -- Semi-Presidentialism: The Rise of an 'Accidental' Model / Sophie Boyron -- Authoritarian Regimes / Po Jen Yap -- Administrative Law Beyond the State: The Influence of International and Supranational Organizations / Giacinto della Cananea -- Administrative Power / Sarah Biddulph -- Separation of Powers in Comparative Perspective: How Much Protection for the Rule of Law? / Peter L. Strauss -- Rule of Law / Giulio Napolitano -- Accountability / Athanasios Psygkas -- Public/Private / Jean-Bernard Auby -- The Germanic Tradition of Comparative Administrative Law / Karl-Peter Sommermann -- Democracy and Authoritarianism / Victor V. Ramraj -- National Executives and Bureaucracies / Matthias Ruffert -- The EU Administrative Institutions, their Law, and Legal Scholarship / Joana Mendes -- Rule-making Regimes in the Modern State / Kevin M. Stack -- A Comparative Approach to Administrative Adjudication / Michael Asimow -- Implementation: Facilitating and Overseeing Public Services at Street Level / Colin Scott -- Through 'Thick' and 'Thin': Comparison in Administrative Law and Regulatory Studies / Elizabeth Fisher -- Administrative Law Values and National Security Functions: Military Detention in the United States and the United Kingdom / Laura A. Dickinson -- Automated Decision-Making and Administrative Law / t
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on December 9, 2020).
Keywords: Administrative law